“For a Long Time Our Voices have been Hushed”: Using Student Perspectives to Develop Supports for Neurodiverse College Students - Gillespie-Lynch, Kristen; Bublitz, Dennis; Donachie, Annemarie; Wong, Vincent; Brooks, Patricia J.; D’Onofrio, Joanne (Frontiers in Psychology, 2017)
Although the challenges that autistic students face adapting to college are often pronounced, they are similar to the challenges that students with other disabilities face (e.g., difficulties with social interaction, self-advocacy, and executive functioning). However, extant evaluations of services for autistic college students are very limited despite an emerging literature examining supports for college students with a range of other disabilities. Given that many autistic students do not self-identify as autistic in college, and consequently might avoid autism-specific services, autistic students might benefit from services that are designed to support a broad range of neurodiverse students, or services that are structured according to the principles of Universal Design. In order to develop such services, we assessed the self-reported needs of autistic college students and their peers with other disabilities. Guided by needs assessments and feedback from students, we developed and evaluated two semesters of mentor-led group programming for autistic college students and students with other disabilities. The first semester of the program focused on social skills; after receiving feedback from participants, the curriculum for the second semester focused on self-advocacy. Participation in social-skills groups was associated with decreased anxiety and autism symptoms. Participation in self-advocacy groups was associated with increased perceived social support from friends, academic self-efficacy, and more accurate definitions of self-advocacy. This research suggests that supports for neurodiverse college students should be developed with their input and should include opportunities to engage with diverse peers.